The Influence of Doses of Rice Husk (Biochar) and Organic Liquid Fertiliser Types on the Growth and Production Yield of Tomatoes (Lycopersicum esculentum Mill) - Napoleão, Marcelino da Costa; Pereira, Inacio Savio; Baptista da Cruz, Marquita Soares (International Journal of Social Service and Research, 2025)
Tomatoes (Lycopersicum esculentum Mill) are essential horticultural crops valued for their high nutritional content and health benefits. With increasing market demand, there is a pressing need to adopt sustainable cultivation practices that enhance soil fertility and crop productivity. This study aims to evaluate the combined effects of rice husk biochar application and different types of liquid fertilizers on tomato yield, with the objective of identifying optimal treatments for improved cultivation. The research employed a Causalized Block Randomized Design (CBRD) with two factors: (1) rice husk application at four levels (0, 1, 2, and 3 tons/ha), and (2) liquid fertilizer type at three levels (no fertilizer, Lof Nachi 500 L/ha, and POC NASA 500 L/ha). Each treatment was replicated three times, resulting in 12 treatment combinations. Data were analyzed using Analysis of Variance (ANOVA). The highest tomato yield (10.76 tons/ha) was observed with the combination of 3 tons/ha rice husk and Lof Nachi 500 L/ha. In contrast, the lowest yield (5.70 tons/ha) occurred in the control treatment without any organic or liquid fertilizer. The results demonstrate a significant interaction between organic matter dosage and liquid fertilizer type in enhancing tomato productivity. This research offers practical implications for sustainable agricultural practices by promoting the integrated use of organic amendments and bio-based fertilizers, which can be particularly beneficial for smallholder farmers seeking cost-effective and eco-friendly production strategies.